The changing nature and role of vocational education and training in Europe : Volume 6: vocationally oriented education and training at higher education levels - expansion and diversification in European countries - (:unkn) unknown (Publications Office of the European Union, 2019)
"This publication is the sixth in a series produced as part of the Cedefop project The changing nature and role of VET (2016-18). Based on analysis of developments over the past two decades (1995-2015), the report provides important insights into developments and change processes related to vocationally oriented education and training at higher levels (levels 5 to 8 of the European qualifications framework). Building on detailed national case studies, the report demonstrates the expansion and diversification of vocationally oriented education and training offered at higher levels in European countries and the variations in how countries use the higher levels: there is evidence for strengthening vocational principles at higher levels in various ways as well as for strengthening academic principles. It also covers current debates and potential future challenges, including juggling labour market demands and wider societal values, finding the right balance between academic and vocational principles, and achieving parity of esteem between academically oriented and vocationally oriented qualifications at higher levels, by improving awareness and visibility of the latter." (Editor; BIBB-Doku)
Keywords: S 2.3 Berufsbildungspolitik; I 2.2 Europa; Berufsbildung; Attraktivität; Berufsbildungspolitik; EU-Bildungspolitik; Höhere Berufsbildung; Berufsbildungsforschung; Europa